2015
DOI: 10.13075/ijomeh.1896.00380
|View full text |Cite
|
Sign up to set email alerts
|

An approach to represent a combined exposure to air pollution

Abstract: Objectives: The objective of this study was to present a technique for estimating the effect of ambient air pollution mix on health outcomes. Material and Methods: We created a technique of indexing air pollution mix as a cause of the increased odds of health problems. As an illustrative example, we analyzed the impact of pollution on the frequency of emergency department (ED) visits due to colitis among young patients (age < 15 years, N = 11 110). Our technique involves 2 steps. First, we considered 6 ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Various methodologies have been advanced to develop multipollutant exposure indexes/metrics to assess multipollutant health effects. For example, Stieb et al [10] and Szyszkowicz [11] developed air quality health indexes based on combinations of air pollutants’ short-term health associations. Coull et al [12] applied Bayesian kernel machine regression that included a hierarchical variable selection function to estimate complex multipollutant health effects and identify important mixture components.…”
Section: Introductionmentioning
confidence: 99%
“…Various methodologies have been advanced to develop multipollutant exposure indexes/metrics to assess multipollutant health effects. For example, Stieb et al [10] and Szyszkowicz [11] developed air quality health indexes based on combinations of air pollutants’ short-term health associations. Coull et al [12] applied Bayesian kernel machine regression that included a hierarchical variable selection function to estimate complex multipollutant health effects and identify important mixture components.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled SO 2 can be easily hydrated to produce sulfurous acid in the respiratory tract, which subsequently dissociates to form its derivatives‐bisulfite and sulfite (1:3 M/M, in neutral fluid), which can be absorbed into blood or other body fluid. Previous studies reported that SO 2 exposure not only induced many respiratory responses, but also linked with many neurological disorders such as migraine headaches and stroke . In addition, SO 2 inhalation can impair learning and memory, and induce differential synaptic injury participated in synaptic transmission and cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly, this is due to the strong correlations between NO 2 and other combustion-derived air pollutants, especially PM. Many studies [ 7 , 14 , 26 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] underline a positive correlation between NO 2 and PM 2.5 . In some studies, NO 2 has been proposed as a surrogate for PM [ 115 , 116 ]; in others, the confounding effects of PM 2.5 are also underlined [ 88 , 117 ].…”
Section: Considerations and Discussionmentioning
confidence: 99%